Energy Spectral Properties of Hydrogen Energetic Neutral Atoms Emitted From the Dayside Atmosphere of Mars. Issue 6 (13th June 2019) - Wang, X.‐D.; Barabash, S.; Futaana, Y.; Shematovich, V.; Galli, A.; Wurz, P.
Abstract: The energy spectrum of hydrogen energetic neutral atoms (HENAs) emitted from the dayside atmosphere of Mars reveals the physical processes of their origin and provides means for remote sensing on the Mars plasma environment. We first compile all available energy spectra of sunward flowing HENA using high‐energy resolution data from the neutral particle detectors on Mars Express from February to June 2004. The median value of the HENA directional flux is 1.12 × 10 5 cm −2 ·s −1 ·sr −1 from 0.3 to 5 keV, making Mars a bright source of HENAs. The energy spectra of the measured HENAs can be approximated by a two‐segment power law spectra. Then we compared the measured statistical energy spectra with those from a kinetic particle transport code. The comparison indicates that the measured HENA energy spectrum is harder (more high‐energy components) than the modeled backscattered HENAs. We propose that a population of sunward‐flowing, charge exchange HENAs produced in the dayside magnetosheath is the most probable reason for this difference. This HENA population with unexpected energy spectrum highlights the kinetic nature of the dayside magnetosheath of Mars. Plain Language Summary: We study the measurements of fast hydrogen atoms moving toward the Sun from the dayside upper atmosphere of Mars. These measurements were done by the neutral particle detectors on Mars Express spacecraft from February to June in 2004. We have got a curve showing how many H atoms move within a certain speed range. This so‐called energy spectrum can tell us where these atoms come from and what has happened to them. Previous studies thought these H atoms are originally protons in the solar wind and are neutralized and scattered by the molecules high in Martian atmosphere. Our study, with the help of computer simulations, shows that the origin is correct, whereas scattering is not enough to explain the observed energy spectrum. We think that the H atoms we detected also contain those from solar wind protons that are deflected by the magnetic field around Mars. This study reveals more insight on how Mars atmosphere reacts to the supersonic solar wind and is related to the bigger question: How did Mars lose most of its atmosphere and water? Key Points: We use two‐segment power laws to fit the energy spectra of sunward‐flowing hydrogen energetic neutral atoms (HENA) observed at Mars Observed HENAs have higher fluxes and more high‐energy component than the modeled backscattered HENAs The more high‐energy component implies additional sources of sunward HENAs, most likely the charge exchange HENAs in the shocked solar wind